Мікротвердість керамічних матеріалів на основі аргіродиту Ag6PS5I, легованого Ge - Філеп Михайло; Filep Mykhailo; Filep Mihály; Погодін Артем; Pogodin Artem; Шендер Ірина; Shender Iryna; Малаховська Тетяна; Malakhovska Tetyana; Біланич Віталій; Vitaliy Bilanych; Кохан Олександр; et al. (My University, 2023)
Резюме. У цій роботі представлено дослідження керамічних матеріалів на основі твердих розчинів Ag6+xP1-xGexS5I (х =0, 0.25, 0.5, 0.75), виготовлених із мікрокристалічних по-рошків. Тверді розчини Ag6+xP1-xGexS5I у формі керамік одержано методом холодного пресування з подальшим відпалом. Мікропорошки твердих розчинів Ag6+xP1-xGexS5I досліджували методом рентгенівського фазового аналізу, а кераміки – вимірюванням мікротвердості. Для всіх досліджуваних керамік спостерігаємо зменшення значень мікротвердості H при зростанні навантаження P, що вказує на присутність прямого розмірного ефекту. За одержаними значеннями індекса Мейєра (n = 1.78 ÷ 1.81) вста-новлено, що досліджувані матеріали належать до м'яких матеріалів.

Abstract. This paper presents the preparation of mic-rocrystalline powders of Ag6PS5I, solid solu-tions of Ag6+xP1-xGexS5I (x = 0.25, 0.5, 0.75) and ceramic materials based on them. The micro-hardness of the ceramic samples was measured and the effect of heterovalent substitution of P5+↔Ge4+ on the mechanical properties of the studied samples was determined.The synthesis of initial Ag6PS5I and neces-sary for doping Ag7GeS5I was performed from the high purity elemental components (Ag, P, Ge, S) and previously synthesized binary AgI. Solid solutions of the Ag6+xP1-xGexS5I (x = 0.25, 0.5, 0.75) composition were synthesized from previously synthesised Ag6PS5I and Ag7GeS5I taken in stoichiometric amounts by a direct one-temperature method. As a result, poly-crystalline bulk alloys of Ag6+xP1-xGexS5I solid were obtained.Microcrystalline Ag6+xP1-xGexS5I powders were obtained from the synthesized polycrys-talline alloys by mechanical grinding (agate mortar). The powders were sieved through sieves with a pore size of 20 μm and 10 μm to obtain a fraction of crystallites with a size of 10-20 μm. The phase composition of the obtained powders was studied by means of XRD method. It has been found that the pow-der patterns of the studied samples are cha-racterized by the presence only of one system of reflexes corresponding to the face-centred cubic cell with SG F-43m.The resulting micropowders were pressed (P ~ 400 MPa) in the form of discs and an-nealed at 650 °С in vacuum quartz ampoules. The microhardness of the ceramics obtained in this way was measured by the Vickers method.For all ceramics, a decrease in the microhard-ness H is observed with an increase in the load P. This indicates that a direct size effect is observed for ceramics made on the basis of solid solutions of Ag6+xP1-xGexS5I. The obtained values of microhardness at a load of P > 1–1.5 Nare independent of the load, which indicates the achievement of intrinsic hardness.Meyer's law was used to further analyze the microhardness and size effect of Ag6+xP1-xGexS5Isolid solutions. The obtained values of the Meyer's index for Ag6+xP1-xGexS5I based ce-ramics are in the range n = 1.78 ÷ 1.81, which demonstrates the implementation of a direct size effect in these samples and indicates that the studied ceramics belong to soft materials. The concentration dependence of the micro-hardness indicates that an increase in the Ger-manium content in ceramic materials of solid solutions of Ag6+xP1-xGexS5I leads to a decrease in the microhardness of the materials.
Microhardness of ceramic materials based on Ge-DOPED ARGYRODITE Ag6PS5I
Редакційна колегія: https://ucj.org.ua/index.php/journal/about/editorialTeam
Keywords: аргіродити; кераміки; мікротвердість